Cognitive Behavioral Counseling with Modelling Pan Balang Tamak to Improve Persuasive - Cipta Ananda, Komang Adi; Dharsana, I Ketut; Suarni, Ni Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This study aimed to determine the effect of cognitive behavioral counseling by modeling techniques Pan balang greedy to increased interest persuasive students through lesson study VIII.4 grade students of SMP Negeri 2 Singaraja. This research is the study design